Errors In Recount Text Made By Tenth Grade Students Of SMA Muhammadiyah 2 Surakarta - Azizah, Dewita Nur; , Prof. Dr. Endang Fauziati, M. Hum; , Nur Hidayat S.Pd., M.Pd (2014)
This study aims at describing the errors made by the tenth grade students of SMA Muhammadiyah 2 Surakarta in their written recount text, identifying the types of morphological errors, syntactical errors and discourse errors, describing the frequency of each type of errors; explaining the dominant type of error, identifying the source of error and explain the pedagogical implication to teaching learning English as foreign language. The type of this research is descriptive qualitative research. Document is used by writer to collect the data. There are three steps to collect the data, namely: the writer gets the data of English composition made by students from teacher, the writer identifies and marks the errors within the text made by students, and the writer classifies the erroneous sentences into a list and used them as the data. The collected data are analyzed by using classification of errors theory, the frequency of type error theory and source of errors theory. The results of this research show that the tenth grade students of SMA Muhammadiyah 2 Surakarta still make 176 errors in their written compositions. The writer finds that from 176 data, there are three classifications of error based on the combination of linguistic category and surface strategy taxonomy. There are morphological that errors consist of 22,71 % including: bound morpheme (-s) as the omission of (-s) in the plural form 4,54 %, misspelling 10,22 %, code switching 5,68 %, and false friend 2,27 %. In the syntactical level, the errors consist of 74,38 % including: omission of BE 7,38 %, misuse of BE 9,09 %, omission of "it" for subjective pronoun 3,40 %, the use of objective pronoun for subjective pronoun 4,54 %, omission of subjective pronoun 1,70 %, misuse of preposition 3,40 %, addition of preposition (to, on) 3,40 %, omission of (-ed) as regular verb 15,34 %, irregular verb 11,36 %, misordering in noun phrase 8,52 % and double marking 6,25 %. And errors in the discourse level consists of 2, 83 % including: anaphoric reference 0,56 % and conjunction 2,27 %. It is derived from 17 types of error. The highest frequency of errors is omission of (-ed) as regular verb. There are 27 errors or 15,34 % from the total number of errors. The researcher also finds sources of error, namely: interlingual transfer and intralingual transfer including ignorance of rules restriction and over generalization.